2020
DOI: 10.29103/jeru.v3i2.3202
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh PDRB Dan Pengeluaran Pemerintah Provinsi Papua Terhadap Kemiskinan Di Papua

Abstract: The purpose of this study was to see the effect of GRDP and Expenditure on the Provincial Government of Papua on Poverty in Papua. The data used in this study are secondary data sourced from the Central Statistics Agency (BPS). The data analysis method used in this study is multiple linear regression with the help of the program package eviews 10. The results showed that the GRDP variable has a negative effect on poverty, while the government expenditure variable does not negatively affect poverty, but togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
3
0
1
Order By: Relevance
“…At α = 10%, the regression coefficient for the government expenditure variable is -0,037, which indicates that if government spending increases, the level of poverty generated will decrease, and on the other hand, if public spending drops, the poverty rate will rise. This study is in line with previous studies (Goni et al, 2022;Rambe 2022;Rarun et al, 2018;Purmini & Rambe, 2021;Pratama & Utama, 2019;Aini, 2020;Megasari et al, 2015;Amalia et al 2015).…”
Section: Effect Of Government Spending On the Povertysupporting
confidence: 93%
“…At α = 10%, the regression coefficient for the government expenditure variable is -0,037, which indicates that if government spending increases, the level of poverty generated will decrease, and on the other hand, if public spending drops, the poverty rate will rise. This study is in line with previous studies (Goni et al, 2022;Rambe 2022;Rarun et al, 2018;Purmini & Rambe, 2021;Pratama & Utama, 2019;Aini, 2020;Megasari et al, 2015;Amalia et al 2015).…”
Section: Effect Of Government Spending On the Povertysupporting
confidence: 93%
“…The opinion expressed by Nicholls (2000), states that rice recipients can determine the level of poverty in the community. The results of this study are relevant to research conducted by Fadhillah et all (2016) and Amalia et All (2016), which reveal that rice recipients influence the number of poor people.…”
Section: The Effect Of Poor Rice Recipients On the Number Of Poor Peoplementioning
confidence: 52%
“…2,000,-/Kg. Amalia et All (2016), conducted research and showed that the number of recipients of poor rice (Raskin) did not influence the poverty rate in the Tringgala village, Sendawa sub-district, Minahasa Regency. Furthermore, research by Maryani (2014), indicates that the Raskin program and the number of Raskin recipients have a significant relationship to the poverty rate.…”
Section: Raskin Rice Recipientsmentioning
confidence: 99%
“…The district government spending has a positive but insignificant effect in reducing the amount of poverty. If people are still living poor, it will interfere with their welfare [30].…”
Section: Alpha = 10%mentioning
confidence: 99%